2017
DOI: 10.18291/njwls.v7i2.81592
|View full text |Cite
|
Sign up to set email alerts
|

On Different Tracks? Gender, Professional Strategies, and Early Career Wage Gaps

Abstract: A longstanding notion in labor market

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Though they aim as high as men and expect to balance work and family, women in these jobs both limit their career and wage prospects (cf. Grönlund, 2017) and perceive more workfamily conflict, since access to flexible work conditions are related to employer demands for constant availability.…”
Section: Discussionmentioning
confidence: 99%
“…Though they aim as high as men and expect to balance work and family, women in these jobs both limit their career and wage prospects (cf. Grönlund, 2017) and perceive more workfamily conflict, since access to flexible work conditions are related to employer demands for constant availability.…”
Section: Discussionmentioning
confidence: 99%
“…However, from another perspective, the increase in the involvement of women in national development, in general and the national labour market, in particular, has created various challenges, including the challenge to ensure a balance between family and vocational responsibilities (Ismail & Abdullah, 2010;Selvaratnam, Padmini, & Kaw, 2011;Grönlund, 2017). For example, a study by Thomson Reuters and the Rockefeller Foundation involving 9,500 women showed that the dilemma between work and family commitments was the greatest challenge faced by 44% of the respondents, especially respondents from Russia, South Korea, India, China and Japan (Hutt, 2015).…”
Section: Problem Statementmentioning
confidence: 99%
“…While most women make trade-offs prioritising home and family over careers (Hakim, 2002(Hakim, , 2006Crompton and Lyonette, 2005), many women in higher level positions make trade-offs in relation to family only in the other direction. For instance, the immense pressures of gendered social norms for women to have families also make many women opt for childlessness as a voluntary life choice (Wager, 2000;Sevón, 2005;Grönlund, 2017). One study, for example, found that most high achieving women had no children (60%) and the rest delayed having children until they achieved high level positions (Eagly and Carli, 2007).…”
Section: Work-life Balancementioning
confidence: 99%